Response of irrigation and sulphur levels on yield and economics of radish grown under drip system in arid region of Rajasthan (Indian Journal of Arid Horticulture, 2025)
Studied the effect of various treatments of drip irrigation (60% PE, 80% PE, 100% PE and 120% PE) and sulphur (Control, 15 kg S ha-1, 30 kg S ha-1 and 45 kg S ha-1) on yield and economics of radish. Among the treatments, the drip irrigation at 100% PE was comparable to 120% PE, yielding the highest root fresh weight (213.09 g), root diameter (4.12 cm), root length (30.11 cm), total fresh weight per plant (291.05 g), yield per hectare (313.93 q ha-1), net returns (₹ 112,969 ha-1), and B:C ratio (3.57). Application of 30 kg S ha-1 resulted in maximum root fresh weight (211.75 g), root length (28.94 cm), and root diameter (3.98 cm), as well as the highest total fresh weight per plant (289.87 g), yield (301.57 q ha-1), and net returns (₹ 106,248 ha-1). The treatment combination of 100% PE irrigation with 30 kg S ha-1 resulted in the highest yield per hectare (331.21 q ha-1), though it was statistically comparable to the treatments of 100% PE with 45 kg S ha-1, 120% PE with 30 kg S ha-1, and 120% PE with 45 kg S ha-1. The radish leaves are rich in minerals, vitamin A (5 IU) and vitamin C (15 mg) and roots are rich in potassium (138 mg) Radish (Raphanus sativus L.) is most popular rabi season root crops which cultivated for its important medicinal and nutritive values. It belongs to Cruciferae family. Being a winter season crop, radish is sown in cool season from mid-September to mid-January in northern plains. Radish is the vegetable of both tropical and temperate regions of the world, widely cultivated for its root, tender leaves and green shoots (Alam et al., 2010). It is rich in diverse amino acids and glucosinolate contents (Xie et al., 2018). Glucosinolates are associated with a reduced cancers risks of the lung, pancreas, stomach, prostate, breast, colon and rectum (Herr and Buchler, 2010). The 100 g of edible roots contain 93.7 per cent water, 1.1 per cent fat and 4.2 per cent carbohydrates.
Keywords: Radish; sulphur; drip irrigation; potential evapotranspiration (PE)